Evaluating the Performance and Institutional Challenges of BMT in North Sumatra: A Multi-Perspective - Yusman; Mustafa Khamal Rokan; Sugianto (Fakultas Ekonomi dan Bisnis Islam, 2024)
Baitul Maal wat Tamwil (BMT) is a Sharia-based microfinance institution that plays a pivotal role in promoting community economic empowerment, particularly in North Sumatra, a region characterized by its rich economic potential and socio-cultural diversity. Despite its strategic importance, many BMTs in this region face persistent challenges, including low levels of Islamic financial literacy, weak institutional governance, limited access to digital technologies, and inadequate working. This study aims to identify the key factors impeding BMT performance and to formulate context-specific revitalization strategies that are both practical and sustainable. Employing a qualitative research design with a case study approach, data were gathered through in-depth interviews, field observations, and document analysis involving three selected BMTs in North Sumatra. Thematic analysis was utilized to uncover critical patterns within the institutional and operational dynamics of these entities. The findings reveal that poor managerial professionalism, declining public trust, and a lack of innovation in Sharia-compliant financial products tailored to local needs are among the primary barriers to performance. In response, this study proposes four strategic recommendations: (1) enhancing human resource capacity through targeted professional training; (2) digitalizing services to foster greater efficiency and transparency; (3) restructuring organizational frameworks; and (4) improving Islamic financial literacy through comprehensive public education initiatives. This research contributes to the development of a locally grounded revitalization model for BMTs, offering actionable insights for practitioners, regulators, and stakeholders committed to advancing an inclusive, resilient, and adaptive Islamic microfinance ecosystem.